EXPRESSION OF CONCERN: Analysis Method of Special Physical Training Mode of Basketball Teams in Colleges Based on WeChat Applet and FTTA Optimised LSTM - Chen, Gang; Zhang, Shuaishuai (EAI Endorsed Transactions on Pervasive Health and Technology, 2024)
Concerns have been raised over the peer review and editorial processes involving this article. The full notice can be found here: https://doi.org/10.4108/eetpht.11.12715